Cytotoxicity of the Ga-containing coatings on biodegradable magnesium alloys. Issue 1 (1st March 2015) - Schmidt, Jürgen; Schrader, Christian; Nguyen, Anika; Weisser, Jürgen; Kunert, Maik; Hort, Norbert
Abstract : Biodegradable magnesium alloys, Mg-0·8wt%Ca and Mg-10wt%Gd, have been coated with gallium-containing electrolyte using plasma electrolytic oxidation (PEO). Thus, the PEO procedure is used as a synthesis tool, to create an appropriate content in the layers. This is a first article on the examination of such layers. One part of the gallium-coated samples was additionally sealed with biodegradable poly(L-lactide-co-caprolactone) (PLLC). Gallium content, morphology and thickness of the coatings were evaluated. Special focus was set in relation to the cytotoxicity of the coating, on the two different magnesium alloys and the additional sealing with PLLC. Cytotoxicity was tested using live/dead staining of MC3T3-E1 fibroblasts and by WST-1 assay, cell differentiation by alkaline phosphatase measurement. It could be shown that the gallium-ion concentration in the PEO layer was higher for Mg-10wt%Gd than that of Mg-0·8wt%Ca, which caused a significant difference in the cytotoxic effects toward MC3T3-E1 cells. Still in all cytotoxic tests, Mg-10wt%Gd showed no to low cytotoxic levels, whereby Mg-0·8wt%Ca showed moderate results. Furthermore, it could be proved that an additional PLLC sealing benefits the cell adhesion and thus promotes the cytocompatibility of the coating.